e-Vehicle booking system at UMP - Najihah, Yaakob (2011)
Currently, vehicle booking system at University Malaysia Pahang (UMP)is done manually.Jabatan Hal Ehwal Pelajar & Alumni (JHEPA) provides the booking form, the applicant need to get the form from JHEPA office and Jabatan Pembangunan & Pengurusan Harta (JPPH) will manage the vehicle booking request made by the applicant.This manual process faced some problem such as use lots of time, space, paper,money and energy.Instead of the applicant difficult to choose suitable vehicle to request,they also have different type of handwriting that can cause misunderstand.JPPH also have conflict to manage the vehicle accurately, like when the paper is cut out or missing.The main aim e-Vehicle Booking at UMP is to help JPPH's management system and also the applicant,the process will be faster and use the web based easily.Some researches have been made to conclude about previous study on booking system include manual, online and mobile application.Software Development Life Cycle(SDLC) method is used from beginning to the end of development of this proposed system.Hopefully this system, with simple application and friendly-user interface will help the applicant in UMP and JPPH staff to do the vehicle booking process easily.